A view of ACC fronts in streamfunction space - Sun, Che; Watts, D. Randolph (Deep Sea Research Part I: Oceanographic Research Papers, 2002)
The fronts and water masses in the Antarctic Circumpolar Current (ACC) are examined with a streamfunction projection of historical hydrographic data. The study shows that only structural criterion provides circumpolarly consistent and time-invariant definition for ACC fronts. The Polar Front position varies little in the streamfunction space, but the Subantarctic Front exhibits significant meridional deflection. Two types of the Antarctic Intermediate Water (AAIW) are identified: the Pacific-Atlantic type represents the recently-formed AAIW through the along-isopycnal subduction of polar surface waters; the Indian-Australian type represents relatively old AAIW which is strongly modified by the Agulhas water. The Subantarctic Mode Water (SAMW) is located in the South Pacific and south of Australia. There is evidence that the SAMW in the southeast Pacific originates from polar surface waters. Therefore the eastward freshening and cooling of SAMW is ascribed to influences from the south. © 2002 Elsevier Science Ltd. All rights reserved.